1971
DOI: 10.3758/bf03210240
|View full text |Cite
|
Sign up to set email alerts
|

The effects of viscosity upon perceived sweetness

Abstract: Six concentrations of sucrose and six concentrations of sodium saccharin were presented as stimuli to 30 Ss. The concentrations were equally spaced logarithmically, covering a 32: I range for each solute. The 12 aqueous solutions were presented at four levels of viscosity, ranging approximately from I to 10,000 centipoises, with sodium carboxymethylcellulose (cellulose gum) as the thickening agent. Magnitude estimates indicate that perceived sweetness decreases with viscosity. In log-log coordinates the Viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 9 publications
4
25
1
Order By: Relevance
“…Previously, it was proved that an increase in taste threshold and a decrease in suprathreshold taste intensity are parallel to the increase in viscosity in which the tastant is dispersed (Arabie & Moskowitz, 1971;Lundgren et al, 1986;Pangborn et al, 1978). However, when a low range of viscosities was analyzed, the effects were rather specific for the gum/compound combination (Pangborn et aI., 1973) and were also found to depend on the pseudoplastic nature of the hydrocolloid (Christensen, 1980a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was proved that an increase in taste threshold and a decrease in suprathreshold taste intensity are parallel to the increase in viscosity in which the tastant is dispersed (Arabie & Moskowitz, 1971;Lundgren et al, 1986;Pangborn et al, 1978). However, when a low range of viscosities was analyzed, the effects were rather specific for the gum/compound combination (Pangborn et aI., 1973) and were also found to depend on the pseudoplastic nature of the hydrocolloid (Christensen, 1980a).…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of water for a thickening or gelling agent generally reduces perceived taste intensity (Arabie & Moskowitz, 1971;Christensen, 1980aChristensen, , 1980bKokini, Bistani, Poole, & Stier, 1982;Pangborn, Gibbs, & Tassan, 1978;Pangborn, Trabue, & Szczesniak, 1973;Stone & Oliver, 1966).…”
mentioning
confidence: 99%
“…For example, increasing the levels of sucrose, citric acid, or sodium chloride has been shown to decrease the perceived viscosities of various solutions (Christensen, 1980b). Correspondingly, increasing the viscosity of a solution can lead to a decrease in both taste and flavor intensity ratings (e.g., Arabie & Moskowitz, 1971;Christensen, 1980a;Cook, Hollowood, Linforth, & Taylor, 2003;Kokini, 1985); this occurs despite the fact that such changes in viscosity have no measurable effect on the concentration of the odorous volatiles released in the nose (Hollowood, Linforth, & Taylor, 2000). It should be noted here that a recent study by Bult, de Wijk, and Hummel (2007) has also demonstrated the reverse interaction between viscosity and flavor: Namely, that the perceived flavor intensity of a liquid can be reduced by increasing its viscosity.…”
Section: Object-based Perceptionmentioning
confidence: 97%
“…In studies by Moskowitz and Arabie (1970) and Arabie and Moskowitz (1971), the method of magnitude estimation was used to scale the perceived taste intensity of citric acid, glucose, quinine sulfate and sodium chloride dissolved in CMC. The perceived tastes of these compounds were shown to decrease continuously with increasing viscosities of CMC from 1 to 1000cps (Moskowitz and Arabie, 1970) and again from 1 to 10000cps (Arabie and Moskowitz, 1971). Pangborn et al (1973), working with extremely low viscosities of gum, found that the sweetness of sucrose, the bitterness of caffeine, and the sourness of citric acid all decreased at viscosities greater than 16cps.…”
Section: Viscosity-taste Interactionsmentioning
confidence: 99%